2019
DOI: 10.3390/su11236682
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric Analysis of the Mass Transport in a Gas Diffusion Layer in PEM Fuel Cells

Abstract: The growth trend of publications in the field of Proton Exchange Membrane Fuel Cell (PEMFC) was analyzed using bibliometric techniques to the identification of the areas with significant development and the orientations that have guided the research on energy cells. This study extracted the data from Scopus and Web of Science (WoS) databases to compare the bibliometric indicators of the published productions. In spite of bibliometric analysis advantages to knowing about the trends in a study area, this researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…To facilitate the visualization of the articles that were excluded during the fi steps, the PRISMA flow diagram [27] (Figure 2) was used. The Methodi Ordinatio is the subject of various publications across many journals, consolidating itself as a process for reviewing knowledge according to delimitations, perceptions of themes and the motivations of researchers and citing the work of Regatieri et al [28], Sarmento et al [29], Sierdovski et al [30], Zahaikevitch et al [31] Cerqueira-Streit et al [32], Thesari et al [33], Lizot et al [34], Buss et al [35], Solis et al [36], Souza et al [37], Bail et al [38] and Soares et al [39].…”
Section: Methodsmentioning
confidence: 99%
“…To facilitate the visualization of the articles that were excluded during the fi steps, the PRISMA flow diagram [27] (Figure 2) was used. The Methodi Ordinatio is the subject of various publications across many journals, consolidating itself as a process for reviewing knowledge according to delimitations, perceptions of themes and the motivations of researchers and citing the work of Regatieri et al [28], Sarmento et al [29], Sierdovski et al [30], Zahaikevitch et al [31] Cerqueira-Streit et al [32], Thesari et al [33], Lizot et al [34], Buss et al [35], Solis et al [36], Souza et al [37], Bail et al [38] and Soares et al [39].…”
Section: Methodsmentioning
confidence: 99%
“…In order to consider not only long-established publications, an alpha value of seven was chosen (Pamplona Solis et al, 2019). An alpha value near to one (α = 1) generates portfolios with classic articles, but if recent papers are more important for the research, then the alpha value should be closer to 10.…”
Section: Methodsmentioning
confidence: 99%
“…The other approach involves focusing on the value chain of the hydrogen economy from an infometrics perspective (bibliometrics and scientometrics), which is based on a paper and/or patent [1, [32][33][34][35][36], or from the evaluation of green energy sources [37][38][39]. Some scholars have presented future research directions by investigating the evolution of hydrogen research regarding production [1, 33,40,41], storage/transportation [33,34,42], and utilization [35,36,[43][44][45][46][47], as discussed in Section 1.1.2. Several studies have revealed the emergence of biohydrogenation, photocatalysis, and water splitting as methods for producing hydrogen from renewable energy sources [1, 33,40,41], thus revealing prominent international cooperation among different countries/regions and institutions [42].…”
Section: Limitations Of the Research On The Hydrogen Economy And Significance Of A Systematic Framework For Implementing The Strategymentioning
confidence: 99%
“…Regarding hydrogen storage/transportation, the development of new hydrogen storage materials was identified as a valuable research field focused on reducing the requirements of implementing hydrogen absorption and desorption [42], and requiring investment [34]. Regarding hydrogen utilization, the studies on FCs, including proton-exchange membrane FCs (PEMFCs) [43,45], solid oxide FCs (SOFCs) [44], and microbial FCs (MFCs) [35], which are considered the next-generation power sources, present the information of the researchers, governments, funding authorities, and investors, as well as the potential collaborative research partners, that could tend toward commercialization. Moreover, the current status of FCEV-related research was investigated to identify the main agents that are involved in scientific and technological research to reveal their collaborative relationships [46] and identify potential R&D opportunities [47].…”
Section: Limitations Of the Research On The Hydrogen Economy And Significance Of A Systematic Framework For Implementing The Strategymentioning
confidence: 99%